2021
DOI: 10.1371/journal.pone.0250456
|View full text |Cite
|
Sign up to set email alerts
|

Calibration and validation of a novel hybrid model of the lumbosacral spine in ArtiSynth–The passive structures

Abstract: In computational biomechanics, two separate types of models have been used predominantly to enhance the understanding of the mechanisms of action of the lumbosacral spine (LSS): Finite element (FE) and musculoskeletal multibody (MB) models. To combine advantages of both models, hybrid FE-MB models are an increasingly used alternative. The aim of this paper is to develop, calibrate, and validate a novel passive hybrid FE-MB open-access simulation model of a ligamentous LSS using ArtiSynth. Based on anatomical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 143 publications
(336 reference statements)
4
23
0
Order By: Relevance
“…The loading model used in the present study was compared with the predicted models in the literature. 13,[24][25][26][27][28][29] During the weight lifting extension, the L3-4 disc experienced a maximum shear load of about 230 N or 0.34 body weight at the flexion position and a maximum compressive load of 1500 N or 2.28 body weight at the upright position. 30 For the patient, the applications in the literature, that can be applied to the spine bone and a 7.5 N.m moment according to the lateral bending, flexion, and torsion with an axial force 400 N of the L3 spine were applied as in Figure 7.…”
Section: Methodsmentioning
confidence: 99%
“…The loading model used in the present study was compared with the predicted models in the literature. 13,[24][25][26][27][28][29] During the weight lifting extension, the L3-4 disc experienced a maximum shear load of about 230 N or 0.34 body weight at the flexion position and a maximum compressive load of 1500 N or 2.28 body weight at the upright position. 30 For the patient, the applications in the literature, that can be applied to the spine bone and a 7.5 N.m moment according to the lateral bending, flexion, and torsion with an axial force 400 N of the L3 spine were applied as in Figure 7.…”
Section: Methodsmentioning
confidence: 99%
“…In 2021, Remus et al [ 47 ] published a passive spine model created with ArtiSynth combining rigid vertebral bodies and deformable IVDs as FEM bodies. In Remus’ work, data were segmented from the VHM [ 67 ] and smoothed.…”
Section: Bidirectional Co-simulation Of the Spinementioning
confidence: 99%
“…By updating the deformation values of the IVDs and the resulting positions of the vertebrae in every increment, updated reaction moments and forces of muscles, tendons and ligaments can be considered. Of the research groups using bidirectional co-simulation models, all authors found that their models were able to deliver accurate results [ 46 , 47 , 73 ]. However, two main methods were identified to bidirectionally couple the MBS and FEM solver.…”
Section: Limitations and Challengesmentioning
confidence: 99%
See 2 more Smart Citations